2011
DOI: 10.1136/thx.2010.148023
|View full text |Cite
|
Sign up to set email alerts
|

Lung function prior to viral lower respiratory tract infections in prematurely born infants

Abstract: Objective Prematurely born infants who develop respiratory syncytial virus (RSV) lower respiratory tract infections (LRTIs) have lung function abnormalities at follow-up. The aim of this study was to determine whether prematurely born infants who developed symptomatic RSV, or other viral LRTI(s), had poorer premorbid lung function than infants who did not develop LRTIs during the RSV season. Methods Lung function (functional residual capacity (FRC), compliance (Crs) and resistance (Rrs) of the respiratory syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 19 publications
2
48
0
3
Order By: Relevance
“…Two studies assessed the role of neonatal lung function in RSV bronchiolitis in prematurely born infants [4,10]. DRYSDALE et al [10] prospectively studied 159 premature born infants that were sampled at each episode of wheeze, cough or shortness of breath. They found impaired neonatal lung function in patients that were hospitalised for a viral lower respiratory tract illness, including RSV, compared with nonhospitalised patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies assessed the role of neonatal lung function in RSV bronchiolitis in prematurely born infants [4,10]. DRYSDALE et al [10] prospectively studied 159 premature born infants that were sampled at each episode of wheeze, cough or shortness of breath. They found impaired neonatal lung function in patients that were hospitalised for a viral lower respiratory tract illness, including RSV, compared with nonhospitalised patients.…”
Section: Discussionmentioning
confidence: 99%
“…Based on this finding, they hypothesised that RSV lower respiratory tract illnesses might be associated with pre-existing lower lung function [9]. The latter association has been found in prematurely born infants [10] and in a high risk population [11]; however, these associations have never been studied in term infants.…”
Section: Introductionmentioning
confidence: 96%
“…Previous genetic studies have demonstrated a significant association between the inherited polymorphisms in several immunological and surfactant protein genes and the incidence of severe viral infection and level of infection-related morbidity among preterm infants [50,51]. Also, pre-existing impairments in lung function have also been attributed to increased susceptibility to severe viral infection and infection-related morbidity among preterm infants, particularly during early life [5254]. …”
Section: Viral Infection Requiring Readmission In Early Lifementioning
confidence: 99%
“…9 Furthermore, diminished lung function in premature infants has been associated with increased likelihood of severe illness. 10 Despite the known increase in hospitalization rates for premature infants with bronchiolitis, little is understood about how or whether their management should differ from that of nonpremature infants. Understanding management differences in premature infants with bronchiolitis is critical because of increasing rates of prematurity.…”
Section: The Clinical Management Of Preterm Infants With Bronchiolitismentioning
confidence: 99%